Public Communication Campaigns 2001
DOI: 10.4135/9781452233260.n28
|View full text |Cite
|
Sign up to set email alerts
|

The Entertainment-Education Strategy in Communication Campaigns

Abstract: I chapter summarizes lessons learned about the use of entertainment-edu " on in communication campaigns dealing with family planning, gender ality, HIV prevention, and environmental conservation. A communication paign (a) intends to achieve specific effects, (b) in a relatively large num of individuals, (c) within a specified period of time, and (d) through an anized set of communication activities (Rogers & Storey, 1987). E ENTERTAINMENT-EDUCATION STRATEGY e entertainment-education strategy abrogates the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 1 publication
2
100
0
Order By: Relevance
“…Hollywood Health & Society in the U.S.) provide creative writers and producers the knowhow to accurately portray critical health information in the popular media. 15 Transmedia storytelling is an innovative media programming trend. 15 Instead of telling the story on a single medium, narrative elements are creatively coordinated across different media platforms (hence "transmedia") to build a story world, engage a broader spectrum of audience, and provide them an enriching experience beyond pure entertainment.…”
Section: Literature Review Transmedia Edutainmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Hollywood Health & Society in the U.S.) provide creative writers and producers the knowhow to accurately portray critical health information in the popular media. 15 Transmedia storytelling is an innovative media programming trend. 15 Instead of telling the story on a single medium, narrative elements are creatively coordinated across different media platforms (hence "transmedia") to build a story world, engage a broader spectrum of audience, and provide them an enriching experience beyond pure entertainment.…”
Section: Literature Review Transmedia Edutainmentmentioning
confidence: 99%
“…In the early days, radio and television dramatic serials were designed and broadcast in Latin America, Asia, and Africa to entertain and educate on a variety of topics. [13][14][15] Using fictional melodramatic narratives, they educated audience about contraceptive methods, modeled positive sexual attitudes and behaviors, and improved the reproductive health of millions in developing countries. [13][14][15] However, edutainment programs in North America and Europe face stiff competition in what represents a media saturated environment.…”
Section: Literature Review Transmedia Edutainmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Brought to you by | MIT Libraries Authenticated Download Date | 5/13/18 7:10 AM In certain entertainment education campaigns, it was found that a subsection of the target group interpreted messages as confirmation of the attitudes and behaviors the campaign was designed to change (Rice and Atkin 1989;Singhal and Rogers 1989; see also Windahl, Signitzer et al 1992;Singhal and Rogers 2001).…”
Section: Behavioral Effects Of Advertising or Commercial Campaignsmentioning
confidence: 99%